Webimar - Adaptive Management at the Strategy Level: Portfolio Reviews and Mid Course Stocktaking - USAID (USAID, 2017)
On Wednesday, November 15, 2017 at 8:00 a.m. EST, the Bureau for Policy, Planning and Learning (PPL) held a one-hour webinar exploring Strategy-level Portfolio Reviews and Mid Course Stocktaking.

+Acumen MOOC: Adaptive Leadership: Mobilizing for Change and Disrupting the Status Quo - +Acumen (NovoEd, 2017)
This four-module course by +Acumen and Adaptive Change Advisors on adaptive leadership, which is a practical leadership framework developed at Harvard Kennedy School for driving systemic change, particularly during times of uncertainty or when there are no easy answers.